Can period-related symptoms predict menstrual manipulation among Australian female cyclists? - Lee, S. J. L.; Peiffer, J. J.; Haakonssen, E.; Van Rens, F. E. C. A. (Journal of Sports Sciences, 2024)
This study explored the extent of menstrual manipulation and its associated impact on period-related symptoms and training disruptions in Australian Female Cyclists. 205 female cyclists, from recreational to elite level, participated in an online "Female Cyclist Questionnaire (FCQ)". The FCQ utilised a series of validated questionnaires to obtain demographic information and menstrual function of the respondents, and to investigate their menstrual manipulation habits and perceptions on how their period-related symptoms affected their well-being, mood, energy and training tolerance. More than 80% of the cyclists reported that their period-related symptoms impacted upon training and 41% made training adjustments based on these symptoms. Two-thirds of respondents thought their training should be phase-controlled yet only half discussed their hormonal cycles with their coaches. Menstrual manipulation was predicted by reduced "workout tolerance" in these cyclists (odds ratio = 0.632). Half of the respondents reported compromised ability to tolerate high-intensity interval training with period-related symptoms. Period pain, increased irritability, lower energy levels and more sugar cravings were commonly reported but did not predict menstrual manipulation. The data indicated that period-related symptoms are present in Australian female cyclists across all levels of participation. However, the perceived impact to training and subsequent behavioural changes varied among individuals.